A Show of Character—a further response to Wiley et al. - Gill, Anthony C.; Mooi, Randall D. (Zootaxa, 2011)
Wiley et al. (2011) begin their critique of our paper (Mooi & Gill, 2010) with an assertion: “we need to make itclear that the foundation of their arguments rests not on scientific rigor, but rather on opinions about the re-classification of fishes using molecular data. This bias is the reason that they only targeted researchers who proposed changes in the higher-level taxonomy of fishes using phylogenetic hypotheses based on DNA sequence data (Miya et al. 2007, Smith & Craig 2007, Thacker 2009). In criticizing these studies, they do not suggest any alternative relationships or provide any counter evidence to the proposed relationships.” And on page 8, they apparently read our thoughts (aside from the title, none of the words in quotations was written by us in that context) and concluded: “Mooi & Gill entitled their paper “A crisis in fish systematics” because they long for the days when “real” ichthyologists found “meaningful” characters and “true” relationships.” Finally (p. 9), they contend that “Mooi & Gill’s various studies are usually focused on Johnson & Patterson’s (1993: 555) “disparate twigs of the [percomorph] tree,” whereas the explicit studies they criticize are large-scale and taxon rich datasets that have not otherwise been analyzed in Percomorpha.”